Current ideas about pathogenesis and treatment of so-called essential epilepsy - Bambaren, Carlos A. (1920)
The role of infections in the genesis of essential epileltsia called, has been held since ancient and contemporary authors as Dercum not hesitate to say that "the role of infections in the production of epilepsy is conclusive evidence." The epileptogenic power, however, has not been understood in all the same manner.